Foreign direct investments, trade policies, and economic growth in Turkey: an ARDL analysis - Bağcı, Rıfgı Buğra; Gökırmak, Haşmet; Gökırmak, Haşmet; Bağcı, Rıfgı Buğra (Pamukkale University, 2020)
Turkish economy experienced a steady growth under a single party administration for the period of 2002 and 2019. An attractive geographical location, a young population, easing of trade barriers, an export lead growth strategy, and political stability attracted large sums of foreign direct investment (FDI) to Turkey during this period. FDI both complements the domestic private investments and makes a rapid technology transfer possible and, hence, stimulates economic development further. This paper aims at exploring impact the FDI and trade openness on the Turkish economy. This study uses the Autoregressive Distributed Lag (ARDL) method to investigate the relationship among real GDP and employment, capital formation, FDI, and trade openness. ARDL analysis results show some evidence of a positive and statistically meaningful effect of employment, FDI, and trade openness on the economic development in Turkey. These results confirm that employment, FDI and trade openness are key factors in economic growth and development for Turkey. Therefore, Turkey should reduce barriers to trade and encourage inflow of FDI in order to finance economic growth and keep up with the technological advancements.

Türkiye ekonomisi 2002 ve 2019 döneminde tek parti yönetimi altında istikrarlı bir büyüme yaşadı. Çekici bir coğrafi konum, genç bir nüfus, ticaret engellerini hafifletilmesi, ihracata dayalı büyüme stratejisi ve siyasi istikrar, bu dönemde büyük miktarda doğrudan yabancı yatırımın (DYY) Türkiye'ye gelmesini sağladı. DYY hem yerel özel yatırımları tamamlamakta hem de hızlı teknoloji transferini mümkün hale getirmektedir ve dolayısıyla ekonomik kalkınmayı daha da teşvik etmektedir. Bu çalışma DYY’nin ve ticarete açık olmanın Türkiye ekonomisi üzerindeki etkilerini araştırmayı amaçlamaktadır. Bu çalışmada, reel GSYİH ile istihdam, sermaye oluşumu, DYY ve ticarete açık olmak arasındaki ilişkiyi araştırmak için Otoregresif Dağıtılmış Gecikme (Autoregressive Distributed Lag-ARDL) yöntemi kullanılmıştır. ARDL analiz sonuçları, istihdamın, doğrudan yabancı yatırımların ve ticarete açık olmanın Türkiye'deki ekonomik kalkınma üzerinde olumlu ve istatistiksel olarak anlamlı bir etkisinin var olduğunu göstermektedir. Bu sonuçlar, istihdam, DYY ve ticarete açık olmanın Türkiye için ekonomik büyüme ve kalkınmada kilit faktörlerden olduklarını doğrulamaktadır. Bu nedenle Türkiye, ekonomik büyümeyi finanse etmek ve teknolojik gelişmelere ayak uydurmak için ticaretin önündeki engelleri azaltmalı ve DYY girişini teşvik etmelidir
Doğrudan yabancı yatırımları, ticaret politikaları ve Türkiye'de ekonomik büyüme: ARDL analizi
JEL codes: O11, O24, F21
Keywords: FDI; Economic development; Trade policy; International investment; Ekonomik kalkınma; Ticaret politikası; Doğrudan yabancı yatırımları